2020
DOI: 10.1109/tmc.2018.2890235
|View full text |Cite
|
Sign up to set email alerts
|

A Complete LTE Mathematical Framework for the Network Slice Planning of the EPC

Abstract: 5G is the next telecommunications standards that will enable the sharing of physical infrastructures to provision ultra short-latency applications, mobile broadband services, Internet of Things, etc. Network slicing is the virtualization technique that is expected to achieve that, as it can allow logical networks to run on top of a common physical infrastructure and ensure service level agreement requirements for different services and applications. In this vein, our paper proposes a novel and complete solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Leland et al studied characteristics of network traffic and found that it has self‐similarity 51 . Other scholars also confirmed this conclusion 52,53 . The Hurst exponent can measure the self‐similarity of the time series.…”
Section: Related Workmentioning
confidence: 90%
“…Leland et al studied characteristics of network traffic and found that it has self‐similarity 51 . Other scholars also confirmed this conclusion 52,53 . The Hurst exponent can measure the self‐similarity of the time series.…”
Section: Related Workmentioning
confidence: 90%
“…One of the most exciting aspects of the adoption of the NS concept is that it enables the automation of the management operations and orchestration of the future networks [2], thus reducing the Operating Expenditures (OPEXs) of the network. Such management operations include to automatically deploy (e.g., SNSs planning) [3] and scale on-demand (e.g., Dynamic Resource Provisioning (DRP)) [4]- [7] network services to cope with the workload fluctuations while guaranteeing the performance requirements. It involves increasing and reducing resources allocated to the services as needed.…”
Section: Single Virtualization Container Like a Virtual Machine (Vm)mentioning
confidence: 99%
“…An initial version of the performance model proposed in this paper was described in our previous work [14]. After, it has been applied to the planning and DRP for specific scenarios in [3] and [6], [7], respectively. All those previous works have reported satisfactory simulation results on the accuracy and usefulness of the model.…”
Section: Contributionsmentioning
confidence: 99%
“…M. Rahman and S. S. Heydari [65] model the number of messages generated at the MME to recover failed sessions in order to evaluate the performance of the self-healing schemes for the failed elements in the CN. J. Prados et al [67], model the control plane traffic of the CN as a G/G/m queue and then calculate the response time of the CN entities in order to resource dimensioning for providing network slice planning. In [68] the authors focus on the MME load and model it with a queuing network.…”
Section: Cn Load Modelingmentioning
confidence: 99%